The Portrayal of Indonesian Women in Advertisements - Yulistiyanti Yulistiyanti; Teguh Kasprabowo (JELLE : Journal Of English Literature, Linguistics, and Education, 2020)
This study examines women images in Indonesian domestic product advertisements. To support this examination, this study also examines the social situations in the advertisements. Soy sauce commercials were taken as the data of this study. It used 17 commercials from three different brands, namely; Kecap ABC, Kecap Bango, and Kecap Sedaap. To conduct this study, it applied sociological approach by using theories on social situation found in Goffman’s Gender Advertisement and women portrayal in commercial in Holtzhausen’s Content Analysis of Roles Portrayed by Women in Advertisements in Selected South African. The data found show that Indonesian product commercials use religious events to promote the products; Ramadhan and Iedhul Adha. The setting of place shows job division between men and women; public area and domestic area. This commercials are dominated by domestic area as the women’s authority. The women image described in the commercials from the female models reflect Indonesian women still hold domestic role as mother and housewive. The data shows 35% as housewives and mothers, 23% as housewives, mothers, and social beings, 18% mothers, 12% housewives, mother, and work-related, 6% as housewives, and 6% as homemakers and social beings. Keywords: Indonesian women, women image, advertisement, social situation, domestic product